The Dramaturgy of Senecan Tragedy - Kohn, Thomas D., 1968- (Book collections on Project MUSE., 2013)
The 1st-century Roman tragedies of Seneca, like all ancient drama, do not contain the sort of external stage directions that we are accustomed to; nevertheless, a careful reading of the plays reveals such stage business as entrances, exits, setting, sound effects, emotions of the characters, and more. This book teases out these dramaturgical elements in Seneca's work and uses them both to aid in the interpretation of the plays and to show the playwright's artistry. The author provides a detailed overview of the corpus, laying the groundwork for appreciating Seneca's techniques in the individual dramas. Each of the chapters explores an individual tragedy in detail, discussing the dramatis personae and examining how the roles would be distributed among a limited number of actors, as well as the identity of the Chorus. The author makes a compelling argument for Seneca as an artist and a dramaturg in the true sense of the word: "a maker of drama." While other scholars have applied this type of performance criticism to individual tragedies or scenes, this comprehensive study is one of the first to consider not just stagecraft, but also metatheatrical issues such as the significant distribution of roles among a limited number of actors, as well as emotional states of the characters. Scholars of classics and theater, as well as those looking to stage the plays, will find much of interest in this study. --